Prospects of Technological Breakthrough of Ukraine: Methods of Assessment and Comparative Analysis - Adamyk, Viktoriia; Dub, Andrij (Herald of Economics, 2026)
The article is devoted to the theoretical substantiation of the methodology for assessing Ukraine’s prospects for a technological breakthrough in the coming years, as well as to the empirical analysis of macroeconomic and scientific-technological prerequisites for technological transformations in several foreign countries. Quantitative assessment of the technological capability of Ukraine and four benchmark countries (Poland, Estonia, Germany, and South Korea) was conducted based on the author’s six-block model of indicators. The blocks cover: digital diffusion, structural transformation, productivity, human capital, capital base, and – as a separate channel – defense-industrial mobilization. The assessment was carried out using the “min-max” normalization method and the multiplicative Cobb-Douglas production function, which served as the basis for developing an integral index of a state’s technological capability. Structural gaps that prevent the transformation of defense-technological advantages into a general economic shift are identified, and priorities for partnership with the EU in the field of innovative development and technology are formulated.